Brain PET in the Diagnosis of Alzheimer’s Disease - Marcus, Charles (Clin Nucl Med, 2014)
OBJECTIVES: The aim of this article was to review the current role of brain PET in the diagnosis of Alzheimer dementia. The characteristic patterns of glucose metabolism on brain FDG-PET can help in differentiating Alzheimer’s disease from other causes of dementia such as frontotemporal dementia and dementia of Lewy body. Amyloid brain PET may exclude significant amyloid deposition and thus Alzheimer’s disease in appropriate clinical setting. CONCLUSIONS: FDG-PET and amyloid PET imaging are valuable in the assessment of patients with Alzheimer’s disease.